Susceptibility genes for lung diseases in the major histocompatibility complex revealed by lung expression quantitative trait loci analysis. Issue 2 (12th May 2016) - Lamontagne, Maxime; Joubert, Philippe; Timens, Wim; Postma, Dirkje S.; Hao, Ke; Nickle, David; Sin, Don D.; Pare, Peter D.; Laviolette, Michel; Bossé, Yohan
The major histocompatibility complex (MHC) has been linked with hundreds of diseases [1]. The MHC is one of the most complex regions of the human genome, because of the high gene density, extended linkage disequilibrium (LD) and sequence diversity [2]. Recent genome-wide association studies (GWAS) have identified polymorphisms located in the MHC that are associated with lung diseases and related traits: asthma, cystic fibrosis, idiopathic interstitial pneumonia, lung cancer and lung function. However, due to the limitations of GWAS and tissue-specific characteristics of gene expression [3], the causal genes and genetic mechanisms mediating the heritable risk within this locus remain to be found. New susceptibility genes for asthma, idiopathic interstitial pneumonia, lung cancer and lung function in the MHC http://ow.ly/10onzl